A Diagnostic Conundrum: Ectopic Nasal Ossification, Submucosal Alveolar Cleft, Absent Posterior Atlantal Arch, and Corpus Callosum Lipoma. (November 2015) - Borumandi, Farzad; Chadha, Ambika; Dediol, Emil; Uglešić, Vedran
A 19-year-old woman was referred for nasal breathing and aesthetic concerns regarding her nose. A computed tomography scan revealed a massive osseous shield anterior to the piriform aperture. Furthermore, there was a submucosal median alveolar cleft, and the posterior arch of C1 was missing. The magnetic resonance imaging brain scan revealed a curvilinear lipoma of corpus callosum. The ectopic nasal bone was removed by open rhinoplast, y and nasal function and aesthetics were restored. The described features defy conventional clinical diagnosis and severity classifications and present a diagnostic conundrum somewhere between a mild form of frontonasal dysplasia, oculoauriculofrontonasal syndrome, and Pai syndrome.